International Patterns and Trends in Endometrial Cancer Incidence, 1978–2013. (16th October 2017) - Lortet-Tieulent, Joannie; Ferlay, Jacques; Bray, Freddie; Jemal, Ahmedin
Abstract: Background: Cancers of the corpus uteri—primarily of the endometrium—rank as the sixth most common neoplasm in women worldwide. Analyses of the global patterns and trends of uterine cancer rates are needed in view of the ongoing obesity epidemic, a major risk factor for the disease. Methods: Data on endometrial cancer (ICD-10 C54) incidence from population-based cancer registries in 43 populations, published in CI5plus or by registries, were extracted for 1978 to 2013. Age-standardized incidence rates were computed for all ages and for pre- (25–49 years) and postmenopausal ages (50 years and older). Temporal trends were assessed with Joinpoint analysis, and the effects of birth cohort and year of diagnosis on the overall trends were examined using age-period-cohort modeling. Results: In 2006 to 2007, rates varied 10-fold across countries. The highest rates were in North America, Eastern and Northern Europe (19 cases per 100 000 among whites in the United States, 95% confidence interval [CI] = 18 to 20, and in Slovakia, 95% CI = 18 to 21), and the lowest rates were in middle-income countries (South Africa 1, 95% CI = 0 to 3, and India 3, 95% CI = 3 to 4). Rates during the most recent 10 data years increased in 26 of the 43 populations considered in this study, with South Africa and several countries in Asia showing the largest increase. The risk of endometrial cancer increased both in consecutive generations and over time in 11 of 23 populations, with the increases more pronounced in Japan, the Philippines, Belarus, Singapore, Costa Rica, and New Zealand. Conclusions: Endometrial cancer incidence rates increased over time and in successive generations in several countries, especially in those countries with rapid socioeconomic transitions.